Infection in Hospitalized Trauma Patients: Prevalence, Risk Factors in Phra Nakhon Si Ayutthaya hospital - Wongreintong, Adisorn (Journal of Preventive Medicine Association of Thailand, 2021)
Several factors place victims of multiple traumas at increased risk for infection. The purpose of this study was to delineate the frequency and risk factors for infection in hospitalized trauma patients. Retrospective surveillance for nosocomial infection was conducted for all trauma patients who were admitted for more than 24 hours in a tertiary care regional trauma center between April 1 and June 30, 2020. A total of 364 patients (300 males) with a mean age of 31 years (range 2-87 years) were reviewed. Most 28.8% sustained close fracture injuries. A total of patients occurred infections was 44 patients (12.1%). Of the hospitalized patients, 69.23% were infected with only one system, 29.23% were dual-infected, and 1.53% was infected with three or more systems. The most common site of infection was lower respiratory tract (60%) followed by surgical site (18.46%) and urinary tract (12.31%). In a multivariate analysis, the risk factors of infection were open fracture (95% CI = 1.69-2.67, p=0.04), extremity injury (95% CI = 1.35-5.35, p < 0.001), ICU admission (95% CI = 1.23-1.57, p < 0.001), ventilated patients (95% CI = 1.83-4.51, p < 0.001), multiple surgical procedures (95% CI = 1.59-4.89, p < 0.001), and received multiple blood transfusions (95% CI = 1.94-1.98, p < 0.001). The first surgical procedure within 24 hours of admission was protective. (95% CI = 0.50-0.67) In conclusion, trauma patients are at high risk for developing an infection. Identifying patients at increased risk for infection may allow for early intervention and subsequent decrease in infectious morbidity.